PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII MTsN 12 PESISIR SELATAN - Okviani Syafti (STKIP Pesisir Selatan, 2020)
The ability to understand mathematical concepts of grade VII students at MTsN 12 Pesisir Selatan has not been satisfactory. Learning that does not provide a memorable learning process and does not involve students in the discovery of mathematical concepts makes the concept only memorized without deep understanding. Discovery learning can facilitate and build students' understanding of mathematical concepts. The purpose of this study was to determine the effect of discovery learning on the ability to understand mathematical concepts of Grade VII students of MTsN 12 Pesisir Selatan based on students' initial abilities. The study population was students of class VII MTsN 12 Pesisir Selatan in the 2017/2018 school year, with the sample of the study being randomly selected, namely class VI.4 students as the experimental class and VII.1 as the control class. This type of research is Quasi Exspriment. The research data were obtained from the results of the initial ability test and the mathematical concept understanding test given after the experiment was carried out. Data analysis using t test. The results of the analysis show that: 1) The ability to understand mathematical concepts of students with high initial ability who are taught discovery learning models is better than students who are taught with conventional learning, 2) The ability to understand mathematical concepts of students with low initial ability who are taught discovery learning models are better than students who are taught with conventional learning.